Popularity, interoperability, and impact of programming languages in 100,000 open source projects - BISSYANDE, Tegawende F. (Institutional Knowledge at Singapore Management University, 2013)
Programming languages have been proposed even before the era of the modern computer. As years have gone, computer resources have increased and application domains have expanded, leading to the proliferation of hundreds of programming languages, each attempting to improve over others or to address new programming paradigms. These languages range from procedural languages like C, object oriented languages like Java, and functional languages such as ML and Haskell. Unfortunately, there is a lack of large scale and comprehensive studies that examine the “popularity”, “interoperability”, and “impact” of various programming languages. To fill this gap, this study investigates a hundred thousands of open source software projects from GitHub to answer various research questions on the “popularity”, “interoperability” and “impact” of various languages measured in different ways (e.g., in terms of lines of code, development teams, issues, etc.).